Kontribusi Manajerial Kepala Sekolah dan Kinerja Guru Terhadap Peningkatan Mutu Pendidikan di SMK Muhammadiyah Prambanan - Erlina Yuliyati; Sedya Santosa (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2020)
The quality of education in schools is influenced by many factors, including the contribution of the principal as a leader that determines whether or not the educational goals achieved at the institution he leads, and the performance of teachers who determine the success of the educational process at school. This study aims to determine whether the improvement of school quality is dominated by the principal managerial contributions and teacher performance, or there are other factors that more strongly influence the improvement of the quality of education in SMK Muhammadiyah Prambanan. This research is a quantitative research with a descriptive approach. Data were collected by a questionnaire involving 43 respondents and then analyzed by multiple regression statistical analysis. The quantitative method as an approach in data analysis is to use SPSS version 17.0 tools. The results of the study and data analysis showed that the managerial variable of principals partially had an effect of 0.944 which meant that there was a strong influence of the managerial variables of principals on improving quality, which was 94.4%. Furthermore, teacher performance variables have an effect of 0.937, which means that 93.7% of teacher performance contributes or significantly influences the quality of education at SMK Muhammadiyah Prambanan. Simultaneously, the contribution of influence given by the managerial variables of school principals and teacher performance to quality improvement was 96.8%, while another 3.2% was influenced by other variables in SMK Muhammadiyah Prambanan. This means that, managerial principals and teacher performance contribute greatly to improving the quality of education in SMK Muhammadiyah Prambanan.